Between Russia and China: Central Asia's transition eperience - Andreas Zeitler (Osteuropa-Institut München, 2005)
The differences in chosen transition paths as well as the resulting outcomes between Russia and China are well-documented. Similarly, the Central Asian republics have followed different transition paths despite similar initial conditions. Kazakhstan, the Kyrgyz Republic and Tajikistan opted for big bang reforms Russian-style while Uzbekistan chose a more gradual way in the Chinese style and Turkmenistan remained principally unreformed. However, the transition outcomes rather resemble the Russian experience. The positive picture of the Uzbek transition highly depended on its relatively modest decline in economic output and social indicators during transition. But with regard to the preservation of the pre-transition output level, Kazakhstan outpaced Uzbekistan in more recent years. With regard to other stylized facts of transition, the developments in the Central Asian republics even more clearly and consistently follow the Russian, not the Chinese, experience. Nevertheless, the slightly different transition experiences, especially between Kazakhstan and Uzbekistan, may be attributable to different institutional developments which are crucial for a smooth transition to a market economy. Uzbekistan avoided the high level of disorganization and disorder evolving in Kazakhstan and the Russian Federation after the demise of political dictatorship and the centrally planned economic system. In this respect, Uzbekistan comes closer to China which may be attributable to a firmer state and far lower rent-seeking opportunities in and around the resource-extracting industries. However, the less profound reform efforts prevented the reallocation of resources which is necessary to guard a successful transition to a market-based economy.
Keywords: 330